Penyuluhan Tentang Cara Pencegahan Penularan TB dan Pemakaian Masker Kepada Keluarga Penderita TB di Johar Baru, Jakarta Pusat - Kholis Ernawati; Rifqatussa’adah Rifqatussa’adah; Rifda Wulansari; Ndaru Andri Damayanti; Titiek Djannatun (Berita Kedokteran Masyarakat (BKM), 2018)
Health education on transmission prevention and use of masks in families with tuberculosis patient: the experience from Johar Baru, Central JakartaPurposeThe objective of the activity is to educate TB patients and families of TB patients about how to prevent TB transmission and the correct use of masks and the use of masks.MethodActivity targets were 35 people from 20 families of TB patients in Johar Baru area, Central Jakarta. Activities carried out were socialization, counseling about the use of masks, giving masks to respondents, and evaluation activities. The extension media used were posters on "5 Ways of TB Prevention" and posters about wearing the correct mask. The counseling was conducted in three visits, ie on February 9, February 10, and February 14, 2017. The counseling was conducted to all families of TB patients who were targeted for the activity.ResultsThe result of the activity shows the education can increase the knowledge of the respondents about the prevention of TB transmission by 85.7%. In addition, it can improve the respondents’ knowledge about how to use masks and practice of mask use by 100%.ConclusionContinuous activity needs to be carried out so that good knowledge can be maintained and is expected to form a positive attitude and later expected to form good hygiene personal behavior.